Thermal modification influences the mechanical resistance of wood from forestry species - Eloy, Elder; Bandera, Eduarda; Mangini, Tauana de Souza; Trevisan, Rômulo; Candaten, Luana; Zanchetta, Laura da Silva (Ciência rural, 2023)
This study evaluated the effects of thermal modification at different temperatures and for different durations on the mechanical strength of wood of selected species from an agroforestry system. To this end, three 9-year-old (approximate age) individuals, each from four species of forest trees-Parapiptadenia rigida (Benth.) Brenan, Peltophorum dubium (Spreng.) Taub., Eucalyptus grandis × Eucalyptus urophylla hybrid, and Schizolobium parahyba (Vell.) Blake-were evaluated. After obtaining initial measurements, samples from the four species under went heat treatment for 2 h and 4 h and were subsequently subjected to heat using an oven at temperatures 120°C, 150°C, 180°C, and 210°C; respectively, in addition to the control. For evaluating mechanical strength, the technical standard ASTM D 143-94 was used to obtain the values of the moduli of elasticity and rupture, tension at the proportional limit, and maximum force of the subjects. It was observed that different durations and temperatures altered the mechanical strength of the wood of the four species studied. The 2 h residence time is the most recommended for conducting thermal modification. This procedure modifies the mechanical resistance of wood in a positive manner, with exposure temperatures ranging between 120 ºC and 180 ºC being the most recommended. The thermal treatment carried out for 4 h is not recommended for structural purposes because of the decrease in flexural strength. RESUMO: O objetivo do presente estudo foi avaliar o efeito da modificação térmica em diferentes tempos e temperaturas na resistência mecânica da madeira de espécies provenientes de um sistema agroflorestal. Para tanto, foram avaliados três indivíduos de Parapiptadenia rigida (Benth.) Brenan, Peltophorum dubium (Spreng.) Taub., Eucalyptus grandis × Eucalyptus urophylla e Schizolobium parahyba (Vell.) Blake, todos com nove anos de idade. Após o dimensionamento, as amostras passaram pelo processo de modificação térmica durante 2h e 4h realizado em estufa nas temperaturas de 120 °C, 150 °C, 180 °C e 210 °C, além da testemunha. Para avaliação da resistência mecânica, seguiu-se a norma técnica ASTM D 143-94, obtendo-se os valores de módulos de elasticidade e ruptura, tensão no limite proporcional e força máxima. Observou-se que os diferentes tempos e temperaturas alteram a resistência mecânica das quatro espécies estudadas. O tempo de 2 h de permanência é o mais recomendado para a realização da modificação térmica. O procedimento modifica a resistência mecânica da madeira de uma forma positiva, sendo que as temperaturas de exposição que variaram entre 120 °C e 180 ºC são as mais recomendadas. A modificação térmica realizada pelo período de 4 h não é recomendada para fins estruturais, pelo fato do decréscimo da resistência à flexão.